LITERATURE REVIEW: SENSITIVITAS OKSIMETRI NADI DALAM MENGENALI GEJALA PENYAKIT JANTUNG BAWAAN KRITIS - Darwanty, Jundra; Yulifah, Rita; Astutik, Heny; Rosmalawati, Ni Wayan Dwi; Yuliani, Ita; Dumilah, Retno (Media Penelitian dan Pengembangan Kesehatan, 2024)
Early detection of Critical Congenital Heart Disease (CCHD) in newborns is crucial to the success of treatment. This underlies the need for pulse oximetry screening as the basis for establishing the diagnosis of CCHD that is not recognized on physical examination. This study aimed to analyze the accuracy of pulse oximetry as a CCHD screening method in newborns. The research method was literature review, data is obtained from the PubMed database with the keywords Critical Congenital Heart Disease (CCHD), Newborn, Screening. The inclusion criteria are that the article is published in 2018-2023, discussing the accuracy of pulse oximetry screening, speaking English, and observational analysis research design. Articles according to the criteria were obtained 80 articles. After going through the selection process, 15 articles were selected. An analysis of 15 articles concluded that pulse oximetry has a high accuracy in assisting in the establishment of the diagnosis of CCHD, indicating the need to include it in routine screening procedures for newborns. However, it must be carried out according to regular procedures, by competent health workers, equipped with adequate facilities and it is necessary to educate prospective parents about CCHD screening during pregnancy to anticipate refusal to undergo treatment if abnormalities are found in the results of pulse oximetry.